An Act to prevent Indians from roaming at large through the Territory, in Compilation of the Public Acts of the Legislative Council of the Territory of Florida, Passed Prior to 1840, at 46 (John P. Duval ed., 1839) - (:unkn) unknown (My University, 1827)
Prohibited any male "Indian" of the years of discretion to leave the reservation assigned to his tribe. Allowed any person or persons to apprehend, seize, and take said "Indian" to some justice of the peace who is "hereby authorized ipowerd, and required" to whip the "Indian" not exceeding thirty-nine stripes. Any gun in possession at the time of apprehension shall be taken and deposited with the authorities.
Keywords: POSSESSION - DANGEROUS PERSONS